Effect of palm oil fuel ash (POFA) for fiber reinforced concrete towards corrosion resistance - Siti Mashitah, Bahrun (2018)
Ordinary Portland Cement (OPC) is well recognized as the major construction material throughout the world. Malaysia is known as the largest exporter of the palm oil. Palm Oil Fuel Ash (POFA) is considered as a waste material produced by burning of fibers, shells and empty fruit brunches. Annually, the quantity of POFA is increased due to the increase of the plantation of palm oil trees in our country. According to the research, the agro waste, such POFA is the pozzolanic material and have the potential to be utilized as construction material by replacing the Ordinary Portland Cement (OPC). In this study, the compressive strength, the durability of corrosion resistance and workability of steel fiber concrete containing Palm Oil Fuel Ash (POFA) were tested. The Ordinary Portland Cement (OPC) was partially replaced with POFA at the dosage of 10%, 20% and 30% by weight of cement used and the control specimen is 100% OPC. From this study, it was found that, the optimum POFA replacement is 20% of cement weight. The strength of POFA concrete has achieved the targeted strength which is 30 N/mm2 compared to OPC. As for the accelerated corrosion test, POFA concrete shows better performance compare to OPC concrete. From the results obtained, it is clear that the partial replacement of cement by POFA beneficial, especially in the construction of concrete.